2010
DOI: 10.1007/s11357-010-9152-x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of 5-HT1A and 5-HT2A positive cells in the brainstems of control age-matched and Alzheimer individuals

Abstract: Serotonin receptor 1A and 2A positive cells in postmortem brainstems were demonstrated via immunohistochemistry in eight control age-matched elderly individuals and eight Alzheimer patients. The 5-HT1A positive cells were found in substantia nigra, pontile nucleus, and vagal as well as dorsal raphe nucleus, while 5-HT2A receptor positive cells were found in motor, sensory and spinal trigeminal nuclei, pontile nucleus, substantia nigra, and nucleus solitarius. A comparison in density of positive cells per unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…In human brainstem, 5-HT 1A and 5-HT 2A positive neurons were found mainly in the substantia nigra, pontine nucleus, the motor vagal and dorsal raphé nucleus, in the sensory, spinal V nuclei, and nucleus solitarius [22]. This strengthens the view that serotonergic related interactions are apparent in the motor, reticular, and sensory nuclei of the brainstem.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…In human brainstem, 5-HT 1A and 5-HT 2A positive neurons were found mainly in the substantia nigra, pontine nucleus, the motor vagal and dorsal raphé nucleus, in the sensory, spinal V nuclei, and nucleus solitarius [22]. This strengthens the view that serotonergic related interactions are apparent in the motor, reticular, and sensory nuclei of the brainstem.…”
supporting
confidence: 75%
“…It has been recorded that at least some of these serotonergic neurons have -aminobutyric acid (GABA) and cholinergic inputs on their cell bodies or dendrites [22]. In our laboratory, we have found that a small percentage of serotonin neurons (no more than 30% of total neurons) also bear its own type of (serotonergic) receptors (1A and 2A) (Fig.…”
mentioning
confidence: 96%
“…All required positive and negative controls were done indicating that used antibodies are specific (data not shown). Antibodies were chosen based on literature (Ramírez et al, 2009 ; Noga et al, 2009 ; Yeung et al, 2010 ; Merlo et al, 2011 ; Hooper et al, 2016 ; Xiao et al, 2016 ). Moreover, we checked the specificity of antibodies by Western Blot, where different levels of receptors protein in different mouse brain structures were observed (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Autopsy of dementia patients reveal normal numbers of 5-HT neurons in the dorsal raphe nuclei (Hendricksen et al, 2004) but abnormal density of 5-HT 1A and 5-HT 2A R (Yeung et al, 2010) in pons and medulla. In the cortex of AD patients 5-HT 1A R alteration was found in correlation with aggressive behaviours (Lai et al, 2003) and a reduced density of 5-HT 4 R expression connected to hyperphagia (Tsang et al, 2010).…”
Section: 5-ht and Respiratory Disordersmentioning
confidence: 99%